PHYSICAL BASIS OF QUASI-OPTIMAL SEISMOACOUSTIC PULSE GENERATING FOR GEOPHYSICAL PROSPECTING IN SHALLOW WATER AND TRANSIT ZONES. PART 1. THEORETICAL FOUNDATIONS - Kudinov Danil S.; Maykov Oleg A.; Balandin Pavel V. (Федеральное государственное автономное образовательное учреждение высшего образования «Сибирский федеральный университет», 2019)
Despite the development of alternative energy, hydrocarbon raw materials is one of the most important energy resources in the world. The discovery of new deposits today is an urgent task. Long-term prospects for the development of seismic exploration are associated with the development of the continental shelf, in particular the Arctic. Also, a large raw material potential is expected from poorly studied territories located on the Arctic coast of the Russian Federation, reef zones of the Persian Gulf states, and in the transit and shallow waters (at a depth of up to 10 meters). The article discusses the theoretical aspects of the excitation of seismic waves in the water, addresses the problems of instrumental implementation of a new source of seismic vibrations that can work: in the water area, in tidal and coastal zones, i.e. produce continuous seismic proﬁling from the water area to the land. The scientiﬁc substantiation of the developed seismic source (SS) design is given.
Keywords: SEISMIC SOURCE; SEISMIC ACOUSTICS; PSEUDO-RANDOM SEQUENCE; SHALLOW WATER; TRANSIT ZONE; СЕЙСМОИСТОЧНИК; СЕЙСМОАКУСТИКА; ПСЕВДОСЛУЧАЙНАЯ ПОСЛЕДОВАТЕЛЬНОСТЬ; МЕЛКОВОДЬЕ; ТРАНЗИТНАЯ ЗОНА; 621.313:621.314